The vagaries of the sea: evidence on the real effects of money from maritime disasters in the Spanish Empire - Adam Brzezinski; Yao Chen; Nuno Palma; Felix Ward (European Historical Economics Society (EHES), 2019)
We exploit a recurring natural experiment to identify the effects of money supply shocks: maritime disasters in the Spanish Empire (1531-1810) that resulted in the loss of substantial amounts of monetary silver. A one percentage point reduction in the money growth rate caused a 1.3% drop in real output that persisted for several years. The empirical evidence highlights nominal rigidities and credit frictions as the primary monetary transmission channels. Our model of the Spanish economy confirms that each of these two channels explain about half of the initial output response, with the credit channel accounting for much of its persistence.
Keywords: E43; E44; E52; N10; N13; 330; Monetary Shocks; Natural Experiment; Nominal Rigidity; Financial Accelerator; DSGE; Minimum-Distance Estimation; Local Projection